Covering Covid-19 pandemic on short video platforms in China: a content analysis of Douyin accounts of people's daily and China daily - Shahrul Nazmi Sannusi,; Normah Mustaffa,; Dongke, Pan (Penerbit Universiti Kebangsaan Malaysia, 2022)
As a new form of social media, short videos have been deeply seated in Chinese life. In order to expand their influence, China's mainstream media also opened accounts on short video platforms, especially during the Covid-19 pandemic. They use short video platforms to report news, which play a key role in guiding public opinion and stabilising people's hearts. Based on the pandemic coverage of two of China's representative media, People's Daily and China Daily on Douyin platform, content analysis method is used to analyse the reporting frequency, video length, reporting content, reporting tendency, and user engagement, and compare the similarities and differences between the two media in the above five aspects. It was found that in terms of reporting frequency, the development trend of the two media is different, but they post roughly the same number of videos per day on average, and the number of videos released during the pandemic is higher than usual. In terms of video length, most of the videos of the two media are produced in a duration of one minute. China Daily produced more long videos than People's Daily. In terms of the reporting content, the two media are involved in 11 constructed categories, but the top four categories are different because of the different position. About the reporting tendency, People's Daily has strong subjective emotion, and China Daily reported more neutral news. As for user engagement, People's Daily did better in likes, comments and shares, although both posted more likes, comments and shares than usual during the pandemic.